2013
DOI: 10.1165/rcmb.2013-0122oc
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 Regulates Leukotrienes to Inhibit Th2-mediated Pulmonary Inflammation

Abstract: Foxa2 is a member of the Forkhead family of nuclear transcription factors that is highly expressed in respiratory epithelial cells of the developing and mature lung. Foxa2 is required for normal airway epithelial differentiation, and its deletion causes goblet-cell metaplasia and Th2-mediated pulmonary inflammation during postnatal development. Foxa2 expression is inhibited during aeroallergen sensitization and after stimulation with Th2 cytokines, when its loss is associated with goblet-cell metaplasia. Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Finally, 19 (58%) subjects had moderate levels (25-75th percentile), and were designated as T1 high/T2 mod. T1 high/T2 low were the youngest (median, 24 yr; interquartile range [IQR], [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and statistically younger than T2 mod. They had the lowest FE NO (median, 16 ppb; IQR, 11-20), were statistically lower than T1 high/T2 high, had the lowest incidence of CRS, highest AQLQ (median, 5; IQR, 4-5.5), highest FEV 1 % predicted (median, 78%; IQR, 71-100), and the lowest rate of ED/hosp.…”
Section: Identification Of a T1-high Severe Asthma Cohortmentioning
confidence: 99%
“…Finally, 19 (58%) subjects had moderate levels (25-75th percentile), and were designated as T1 high/T2 mod. T1 high/T2 low were the youngest (median, 24 yr; interquartile range [IQR], [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and statistically younger than T2 mod. They had the lowest FE NO (median, 16 ppb; IQR, 11-20), were statistically lower than T1 high/T2 high, had the lowest incidence of CRS, highest AQLQ (median, 5; IQR, 4-5.5), highest FEV 1 % predicted (median, 78%; IQR, 71-100), and the lowest rate of ED/hosp.…”
Section: Identification Of a T1-high Severe Asthma Cohortmentioning
confidence: 99%
“…In the developing lung, it regulates epithelial differentiation and controls goblet cell hyperplasia. It also has immunoregulatory functions and limits type-2 immunity through inhibition of the cysteinyl LT signaling pathway (83,141,144).…”
Section: Factors Influencing the Development And Maturation Of Lung Imentioning
confidence: 99%
“…SAM-pointed domain, a transcription factors containing ETS like factor (SPDEF) and forkhead box protein A2 (FOXA2), regulates the differentiation of goblet cells. Airway mucin 5AC, secreted by SPDEF, is aggravated the differentiation of goblet cells and mucin production ( Park et al, 2007 ; Chen et al, 2009 ; Rajavelu et al, 2015 ), while FOXA2 effectively inhibited the differentiation of pulmonary goblet cells ( Tang et al, 2013 ). Song et al (2017) had found hypermethylation of CPG-8 in the promoter of SPDEF and hypomethylation of CpG-14 and CpG-15 in FOXA2 , was identified the abnormal methylation of SPDEF and FOXA2 during the differentiation of goblet cells is the basic factor of mucus hypersecretion in COPD, thus providing a new approach to understand mucus hypersecretion from the perspective of epigenetics.…”
Section: Biomarker In Tracheal Epithelium and Lung Tissuementioning
confidence: 99%